A generalized contact potential and its application in discontinuous deformation analysis. (July 2018) - Fan, Huo; Zheng, Hong; Wang, Jianfeng
Abstract: The distributed contact force that is determined from the contact potential can be used to deal with the contact between discrete bodies. The current study defines the generalized contact potential (GCP). The GCP is independent of the shape and size of body and possesses the thorough geometric locality. If and only if the contact regions are exactly the same, the contact potentials are identical. By combining discontinuous deformation analysis (DDA) and GCP a new DDA, named GCP-DDA, is produced, in which the generalized- α method is adopted to discretize the time domain. The GCP-DDA can make the global controlling equation and the open-close iteration (OCI), which may cause the reduction of time step size and the rebuilding and solving of global controlling equation, become unnecessary. The intractable issues related to convex-convex contact in the original DDA can be accordingly bypassed.